A neonatal murine model of coxsackievirus A4 infection for evaluation of vaccines and antiviral drugs. Issue 1 (1st January 2019) - Zhang, Zhenjie; Zhang, Xingcheng; Carr, Michael J.; Zhou, Hong; Li, Juan; Liu, Shaoqiong; Liu, Tao; Xing, Weijia; Shi, Weifeng
ABSTRACT: Coxsackievirus A4 (CVA4) infection can cause hand, foot and mouth disease (HFMD), an epidemic illness affecting neonatal and paediatric cohorts, which can develop to severe neurological disease with high mortality. In this study, we established the first ICR mouse model of CVA4 infection for the evaluation of inactivated vaccines and antiviral drug screening. The CVA4 YT226R strain was selected to infect the neonatal mice and three infectious factors were optimized to establish the infection model. The 3-day-old neonatal mice exhibited clinical symptoms such as hind limb paralysis and death. The severe inflammatory reactions were closely related to the abnormal expression of the acute phase response proinflammatory cytokine IL-6 and an imbalance in the IFN-γ/IL-4 ratio. Importantly, the inactivated CVA4 whole-virus vaccine induced humoral immune responses in adult females and the maternal antibodies afforded mice complete protection against lethal dose challenges of homologous or heterologous CVA4 strains. Both IFN-α2a and antiserum inhibited the replication of CVA4 and increased the survival rates of neonatal mice during the early stages of infection. This neonatal murine model of CVA4 infection will be useful for the development of prophylactic and therapeutic vaccines and for screening of antiviral drugs targeting CVA4 to decrease morbidity and mortality.